2000
DOI: 10.1086/318117
|View full text |Cite
|
Sign up to set email alerts
|

Large Outbreak in a Surgical Intensive Care Unit of Colonization or Infection withPseudomonas aeruginosathat Overexpressed an Active Efflux Pump

Abstract: During a 30-month survey, 55 patients were colonized or infected by a single clone of Pseudomonas aeruginosa in a surgical intensive care unit (ICU). This clone overexpressed an efflux pump system, and its antibiotic resistance pattern was extremely stable as it spread from patient to patient. Pulsed-field gel electrophoresis showed that isolates from different patients were genetically identical or very similar. We were unable to identify an environmental reservoir, but cultures of hand specimens from 2 healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 22 publications
2
27
0
3
Order By: Relevance
“…While a few previous studies have reported on the clonal spread of P. aeruginosa isolates overexpressing an efflux pump (3,12), to the best of our knowledge, this is the first description of an outbreak caused by a P. aeruginosa strain that simultaneously hyperproduced MexXY-OprM and produced an integron-borne PSE-1 ␤-lactamase. These two resistance mechanisms have previously been reported among P. aeruginosa isolates that are more resistant to FEP than to CAZ (16).…”
Section: Discussionmentioning
confidence: 70%
“…While a few previous studies have reported on the clonal spread of P. aeruginosa isolates overexpressing an efflux pump (3,12), to the best of our knowledge, this is the first description of an outbreak caused by a P. aeruginosa strain that simultaneously hyperproduced MexXY-OprM and produced an integron-borne PSE-1 ␤-lactamase. These two resistance mechanisms have previously been reported among P. aeruginosa isolates that are more resistant to FEP than to CAZ (16).…”
Section: Discussionmentioning
confidence: 70%
“…During the survey period, 201 patients admitted to the hospital in Besançon were colonized and/or infected by an epidemic clone of P. aeruginosa serotype O:6. The outbreak was initially detected in the surgical ICU in May 1999 (8). However, a retrospective study showed that the epidemic strain was already present in the institution in May 1997.…”
Section: Resultsmentioning
confidence: 99%
“…We recently witnessed the propagation of a multiresistant P. aeruginosa epidemic clone in the surgical intensive care unit (ICU) of the Besançon public hospital, France (8). The outbreak was controlled in the ward after implementation of strict hygiene measures but has disseminated inside and outside the hospital since then, affecting more than 200 patients.…”
mentioning
confidence: 99%
“…Bearing in mind that the probability of developing resistance during treatment is close to 10% [5], it is possible that a patient having a longer stay in hospital and greater exposure to different antibiotics [18], sequencially [7], may develop resistance, especially in the context of cross transmission in a small unit [16]. Bertrand et al, have described a large-scale epidemic in a surgical ICU which lasted 55 months [19]. No environmental reservoir was identified, but colonisation of health personnel's hands was documented.…”
Section: Discussionmentioning
confidence: 99%